231k views
4 votes
(2x - 1)/3 = -4xWhat is X

User Seesharper
by
4.7k points

1 Answer

0 votes

We are given the following expression to solve for x.


(\mleft(2x-1\mright))/(3)=-4x

Multiply both sides of the equation by 3


\begin{gathered} (3(2x-1))/(3)=3*-4x \\ 2x-1=-12x \end{gathered}

Now combine the like terms (bring the term 12x to the left and the term 1 to the right)

When you move a term to either side of the equation then its sign gets reversed


\begin{gathered} 2x-1=-12x \\ 2x+12x=1 \\ 14x=1 \\ x=(1)/(14) \end{gathered}

Therefore, x is equal to 1/14

User Danny Rancher
by
5.1k points